ISLAM DI TENGAH PUTARAN GLOBAL - Angga Teguh Prasetya (El-QUDWAH, 2013)
Islam di tengah Putaran Masyarakat Global Oleh: Angga Teguh Prastyo  Abstract Islam and civilization interconnected one another. Civilization is result of good Islam. While certifiable Islamis result of awareness of civilized civilization. So, it is important to plan Islam which has positive contribution of development of civilization. Everything that owned by human being such as heart, soul, mind, ear, feet, hand, have potency to equip existing of civilization or even create modern civilization. Hearth and mind for example, are the source of human being for being attitude and decide policy. Hearth and mind require benefaction values so that a clarification value of civilization will grow from them. Process mind and hearth have a meaning to build resources of human being. Islam is succes if resources of human being is built maximally and ever can boost up prestige of human being it self. If measured with scale, mind and hearth which are the first time on zero it can be turn into ten getting education. That is the real Islam which can be told succeed. Forming an Islam system which be able to process and utilize capable to process and utiliable both of that human being potency is an obligation which have to be done. Both of them have potency to lift the quality of Indonesia human resources to be better. Both of them  are fundamental element of every human being. Heart and mind solidarity will be behaviour. Behaviuor is coherent kindness image in each human. Besides that, behaviour also have a function as kind hearted maturity symbol of human being. Because of becoming identity, duty of the first time is how behaviour becomes  positive identity it self. Therefore, without behavior, human lose its spirit.   Keywords: Islam, the global community, the Muslim